Metabolic profiling and transcriptomic data providing critical flavonoid biosynthesis mechanisms disclose color differences of purple heading Chinese cabbages (Brassica rapa L.). (1st October 2022) - He, Qiong; Xue, Yihua; Wang, Yaxiu; Zhang, Ninan; Zhang, Lugang
Abstract: Flavonoids are important secondary metabolites; however, detailed flavonoids and related biosynthesis mechanisms of purple heading Chinese cabbages (PHCCs) with different purple colors still remain largely unclear. Here, we conducted a combined metabolome and transcriptome analysis; thereinto, 102 flavonoids including 12 anthocyanins, 6 flavanols, 18 flavanones, 37 flavones, 22 flavonols, 6 isoflavones, and one proanthocyanidin, were first identified. Gallocatechin-gallocatechin, hesperetin C-hexosyl-O-hexosyl-O-hexoside, and tricin O-saccharic acid were main flavonoids, whereas cyanidin 3, 5-O-diglucoside, delphinidin 3-O-glucoside, cyanidin 3-O-glucoside, and pelargonidin 3-O-beta-D-glucoside were main anthocyanins. Cyanidin 3, 5-O-diglucoside, pelargonidin 3-O-beta-D-glucoside, and cyanidin O-syringic acid directly affected color differences in both different positions and identical position comparisons of two PHCCs. The main difference occurred in the middle leaf-head; meanwhile, 323 flavonoid biosynthesis genes (FBGs) were first identified, including 204 differentially expressed genes. An integrative correlation analysis among them showed that some FBGs were more closely connected with flavonoid content. The promoted BrMYB2 played an important role regarding anthocyanins' production in PHCCs, whereas key BrTT8 and BrMYBL2.1, and other factors might synergistically response to form color differences, together with a series of active structural FBGs ( BrCHS s, BrCHI s, BrF3H1, BrF3′H, BrDFR1, BrANS1, BrUGT s, BrAT s, and BrGST s) participated. These results provided valuable clues for understanding flavonoid biosynthesis in Brassica crops. Graphical abstract: Image 1 Highlights: Flavonoid biosynthesis mechanisms of purple heading Chinese cabbages were first acquired. A total of 204 DEGs and 71 DAFs referring to flavonoid biosynthesis were identified. A pelargonidin and 6 cyanidins directly affected color difference of purple heading Chinese cabbage. BrMYB2 played an important role in the production of anthocyanins of purple heading Chinese cabbage. BrMYB2, BrTT8 and BrMYBL2.1, and structural flavonoid DEGs together affected the color difference.